Tongging Hotel Resort With Neo Vernacular Approach - Firman Eddy; Dariyan Arya Wijaya (Talenta Publisher, 2020)
Indonesian’s nature has a combination of a tropical climate and is the largest and most island nation in the world. Indonesia also has many natural tourism sites that are already well-known abroad. One of them is Lake Toba. Lake Toba is the largest and deepest lake in Southeast Asia. These tourist attractions are also supported by a cultural heritage that is rich with many tribes and customs that spread throughout Indonesia. Resort hotels are one of the supporting facilities in the tourist area. The design of the Tongging resort hotel raises the theme of neo vernacular. The problem posed was